Chronicles - December 2005 - Sugiharto, Bambang; Tedjoworo, Hadrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2005)
'Chronicles' is a journal column of "MELINTAS" which contains information about the various events, congresses, conferences, symposia, necrologies, publications, and periodicals in the fields of philosophy and theology.